Внутригородские некрополи конца Х-XIV вв. Как элемент исторической топографии византийского Херсона - Иванов, А. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Ivanov. Inner City Cemeteries End of X—XIV ct. as a Element of the Historical Topography of Byzantine ChersonThe publication is devoted to the history of the occurrence and topography of the inner city necropolis of the Byzantine Kherson. The consideration objects are formed in the city at a relatively late stage of its existence no earlier than the turn of the X—XI centuries. And mainly function to the demise of the urban settlement. Their appearance is made possible by the changes occurred in the practice of Christian burial rites peculiar to the Byzantine world in general. With respect to those expressed in Kherson in overcoming age-old traditions of a country cemetery, and later placing most of the funerary complexes inside the city walls. Placement of cemeteries within the previously formed urban development presents certain problems and allowed the use of a desolate areas previously occupied buildings so narrow-minded areas of major church complexes, for various reasons have ceased to exist at the turn of the X—XI centuries.Key words: Herson, city, topography, necropolis, Сhristianity.